Analisis Rantai Pasok (Supply Chain) Komoditas Ayam Cemani (Studi Kasus Di Pakis, Kota Malang, Jawa Timur) - Alfian Adi Atma; Wenny Ladhunka Nur Aliyya; Wahyuni Wahyuni (Fakultas Peternakan Universitas Tulang Bawang Lampung, 2022)
ABSTRACT Chicken Cemani is a local Indonesian chicken that has been worldwide. The potential of Cemani chicken is very good, apart from being a chicken used for traditional ceremonies, Cemani chicken has good production potential and has very large export prospects. However, the population is still limited causing many requests that cannot be fulfilled. Maintenance that has not implemented an integrated and traditional supply chain system causes the development of Cemani chicken agribusiness to be slow. The supply chain management system (SCM) is an integrated marketing system that includes the integration of products and actors to provide satisfaction to customers. In the Cemani chicken commodity, the actors and those involved are not clearly known. This study aims to determine the actors involved in the Cemani chicken supply chain and to find out the product flow, as well as the finances contained in the supply chain in Pakis, Malang, East Java. The study was conducted at the Cemani chicken farm in Pakis, Malang, East Java. The location selection was done purposively based on the consideration that the center of the Cemani chicken farm in Indonesia was in Pakis, Malang City, East Java. The research was conducted in November 2020. The research method used is a descriptive survey method. The method of determining respondents is purposive sampling which is based on the supply chain of a farm owned by Mr. Ihsan and Mr. Sigit. Determination of the respondents of traders and consumers in this study was carried out by snowball sampling, namely tracing the supply chain channels of the livestock owned by Mr. Ihsan and Mr. Sigit from traders to consumers in the Java area. Respondents in this study were 2 breeders. The data for product flow obtained were analyzed descriptively while for financial flows were analyzed using margin and efficiency analysis. Based on the results of the study, it is known that the actors in the supply chain of grade I and grade I Cemani chickens are breeders, traders in the city, traders outside the city and consumers. There are three marketing channels in the marketing supply chain for Cemani chicken in Pakis Malang City, namely channel I consisting of Breeders → Traders Outside Malang City → Traders in the City → Consumers. Channel II consists of Farmers → Traders in the City → Consumers and channel III consists of Farmers → Consumers. Sales use online and offline systems. The flow of finance where the selling price is the highest is the out-of-town traders belonging to Mr. Sigit at a price of Rp. 350,000 – Rp. 531,250 / head with the age of 2-5 months. The most efficient marketing channel is that farmers distribute directly to consumers. Keyword : Products flow, financial flow, local chicken